Wpływ czynników niematerialnych na wartość rynkową przedsiębiorstw - Paździor, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main goal of almost every company is increasing its market value. However, some companies, especially small, provide politics of maximizing profit in a short term. Managers of large corporations attach more importance to the factors which determin market value of an enterprise. These factors could be divided into two separate groups: tangible and intangible. Examples of the largest companies in the world show that intangible factors are more important in creating value process than wgible ones. Empirical study enclosed in this article, based on the Polish joint-stock companies, also confirms facts observed in well developed countries. Based on the results of this empirical study, it can be said that market value of the Polish public companies is also determined in a high level by the intangible factors like a human capital and special structure of an organization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 414-423